Influence of precipitating and solvent on the formation of antimony tetraoxide catalyst. - Abdul Rahman, Mohd Basyaruddin; Saiman, Mohd Izham; Ramli, Irmawati; Abdullah, Abdul Halim (2007)

(untitled)
Antimony oxide has found application in various area including clarification, pigment, material synthesis and catalyst. This study investigated the influence of synthesis parameters (precipitating agent and solvent) on the formation of antimony oxide powder. Characterizations of the samples were carried out by Thermogravimetry Analysis (TGA), X-Ray Diffraction (XRD), Fourier Transform Infrared (FTIR) spectroscopy, BET surface area measurement and Scanning Electron Microscopy (SEM). Investigations on the influence of the type of precipitating agents (NaOH and NH4OH), on the formation of antimony oxide revealed that -Sb2O4 was produced after the precursors were calcined. The precursors were a mixture of Sb4O5Cl2 and Sb2O3 phase when precipitated with NaOH but only Sb2O3 phase when precipitated with NH4OH. By varying the concentration two precipitation agent, NH4OH solution gave higher surface area and fine morphologies for the samples compared to NaOH solution. On the influence of solvent, ethanol gave full reflection of Sb2O3 and different structure phase before calcination process. No phase of the antimony oxy chloride was obtained for these samples. After calcined process, all samples gave full reflection of the -Sb2O4. Usage of the NaOH as a precipitating agent gave higher surface area compared to NH4OH samples.